Optimizing oral vaccines: induction of systemic and mucosal B-cell and antibody responses to tetanus toxoid by use of cholera toxin as an adjuvant. - Jackson, R J (1993)
Cholera toxin (CT) is an effective mucosal antigen and acts as an adjuvant when given orally with various antigens; however, few studies have compared the levels of antibody responses to CT and coadministered protein in systemic and mucosal tissues. In this study, we used tetanus toxoid (TT) for assessment of immune responses. Time course and dose-response studies established that 250 micrograms of TT given orally with 10 micrograms of CT three times at weekly intervals induced high serum and gastrointestinal tract anti-TT and anti-CT antibody responses. Oral immunization with TT alone induced no detectable mucosal immunoglobulin A (IgA) antibodies in fecal extracts and only weak serum IgG anti-TT responses. The coadministration of CT and TT induced peak serum IgG anti-TT responses following two oral doses that remained constant after the third oral immunization, while optimal mucosal IgA responses were seen after the third oral immunization. The serum anti-TT response obtained with CT and TT proved protective against TT challenge (100 minimum lethal doses), whereas mice orally given CT or TT alone died. Antigen-specific B-cell responses were assessed with an isotype-specific Elispot assay of isolated lymphoid cells from the spleen, Peyer's patches, and the small intestinal lamina propria. Interestingly, approximately fourfold-higher numbers of IgA anti-CT than of anti-TT antibody-producing (spot-forming) cells occurred in lymphocytes from the lamina propria of mice orally immunized with both TT and CT. The adjuvant CT did not induce polyclonal B-cell responses in mice given CT by the oral route, since no significant differences in total numbers of B cells producing IgA, IgG, or IgM were found compared with the numbers in mice given TT alone. The results clearly indicate that serum and mucosal antibody responses develop with different kinetics and that protective TT-specific antibody responses are generated in the systemic compartment when TT is administered with CT via the oral route.